Native Metallophytes on Ultramafic Wooded Grassland in Sta Cruz, Mindoro Occidental, Philippines: Insights Into Phytostabilization and Forest Restoration - Quimado, Marilyn Ong; Hernandez, Jonathan Ogayon; Tinio, Crusty Estoque; Cambel, Maria Patrice Salazar; Luna, Amelita Carpio; Fernando, Edwino Sanson (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2023)
The native metallophytes species are the optimum choice to restore degraded areas on ultramafic soil. However, a limited restorative floristic survey on the wooded grassland of Mindoro Occidental had been reported. Four 20 m x 20 m plots were established to rapidly assess the plant diversity of a wooded grassland on ultramafic soil in Sta. Cruz, Mindoro Occidental, Philippines. Diversity index (H`), relative density, relative dominance, and importance value (IV) were computed. Physicochemical characteristics and heavy metal contents of the soil in the site were analytically determined. We identified 43 morpho-species of plants belonging to 25 families. Thirty-six of the morpho-species identified are Philippine natives and typically grow on ultramafic forests. Nine species out of the top 10 trees with the highest IV are native ones, with Buchanania arborescens Blume as the most dominant. The estimate of Relative Cover (%) also showed native species. Poles and sapling dominated the area, suggesting that active regeneration is taking place. Further, 72.94% of the ground cover were represented by tree flora recruits (e.g., B. arborescens, Alstonia macrophylla). The sites have overall moderate diversity (H` index of 2.7). The soil contains a high amount of Nickel, Chromium, Iron, and Manganese. There were no Nickel hyperaccumulators but 22 native species showed Aluminum and Silicon hyperaccumulation. Therefore, the study revealed that the surveyed area is home to important metallophytes that have the potential for phytostabilization and reforestation.